(untitled) (AYUSHDHARA, 2025)
Today is the era of modernization and everybody is busy and living stressful life. A variety of health problems might arise from people developing behaviors that discourage them from being active and encourage a sedentary lifestyle. Some of the factors that contribute to chronic non-communicable diseases, which can have near-fatal outcomes, include stress, eating fast food, and not exercising. The burden of metabolic disorders is increasing due to the significant changes that have occurred in daily living during the past century. Hyperlipidemia is one of them, which is potential risk factor for multiple disease like atherosclerosis, metabolic syndrome and even hypertension. The term "hyperlipidemia" refers to elevated serum levels of either triglycerides or cholesterol, or both. In Ayurvedic literature, hyperlipidemia is discussed as Medovriddhi, Rasagata Sneha Vriddhi, and Rasa Raktagata Sneha Vriddhi, among other names. When kept in the body for a prolonged period of time, hyperlipidemia is the same as increased Asthayi Sama Medo Dhatu and causes difficulties. While describing the treatment of Medovaha Srotas vikar, I select the drug Musta. It is mentioned in Lekhaneeya Dashemani dravyas. The medicine was chosen due to its wide availability, affordability, and variety of applications.